Analysis Of Employee Data System The National Narcotics Argency Of South Sumatera Selatan - Gita Rohana; Apriansyah (Yayasan Pendidikan Rafisqy Arfadhia, 2022)
The development of science and technology, especially in the field of information technology, has brought great changes to the development of information or agency, the development of information technology can be used to support organizational activities in goverment agencies are always in touch with the community, the development of information technology ca be used optimize public service to be more effective and efficient. Utilization of information technology in a goverment organization is increasingly needed, including in the national narcotics agency. Because in improving sector services to support the goverment’s role in public administration, because very rapud technological developments lead an agency to obtain information more quickly and accurately. With the existence of an integrated information system for data management, it will facilitate of the performance of employees at the national narcotics agency.